Day 2 Tue, April 17, 2018 2018
DOI: 10.2118/190550-ms
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Development Goals Atlas

Abstract: In 2017, the United Nations Development Programme (UNDP), International Finance Corporation (IFC) and IPIECA released a joint report, Mapping the Oil and Gas Industry to the SDGs: An Atlas (from here on referred to as the Atlas). The Atlas focuses on creating a shared understanding of the implications of the UN Sustainable Development Goals (SDGs) for the oil and gas industry and how the industry can most effectively contribute to their achievement. The Atlas offers an overview of opportunities and challenges,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
1
2
0
Order By: Relevance
“…The long‐term commitment put in place by ALFA enabled the logic of sustainability to be fully integrated in all the design and construction phases of the transmission lines. From this point of view, in accordance with Mire et al (2018) and Ite (2018), the SDGs represent the lens through which the concrete effects of this integration process can be outlined and measured, revealing the consequent effects at the local level. Moreover, from an accountability perspective, this vision of the SDGs also represents an opportunity to support the reporting and communication of corporate sustainability, both intensifying this practice (Shoaf et al, 2018; Thorlakson et al, 2018; Verdolini et al, 2018), and increasing its transparency and credibility (Agarchand & Laishram, 2017; Anasi et al, 2018).…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…The long‐term commitment put in place by ALFA enabled the logic of sustainability to be fully integrated in all the design and construction phases of the transmission lines. From this point of view, in accordance with Mire et al (2018) and Ite (2018), the SDGs represent the lens through which the concrete effects of this integration process can be outlined and measured, revealing the consequent effects at the local level. Moreover, from an accountability perspective, this vision of the SDGs also represents an opportunity to support the reporting and communication of corporate sustainability, both intensifying this practice (Shoaf et al, 2018; Thorlakson et al, 2018; Verdolini et al, 2018), and increasing its transparency and credibility (Agarchand & Laishram, 2017; Anasi et al, 2018).…”
Section: Discussionsupporting
confidence: 56%
“…The case seems to provide a new interpretive model for the SDGs on the integration of sustainability. It enriches the existing literature (Mire et al, 2018;Scheyvens et al, 2016) by identifying SDGs as a guiding tool both for policies and operations. In term of managerial implications, we found that the SDGs can enable top managers to design strategies in accordance with sustainability priorities defined on a global scale.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation